Deaths in people from Black, Asian and minority ethnic communities from both COVID-19 and non-COVID causes in the first weeks of the pandemic in London: a hospital case note review. Issue 10 (16th October 2020) - Perkin, Michael Richard; Heap, Sarah; Crerar-Gilbert, Agatha; Albuquerque, Wendy; Haywood, Serena; Avila, Zoe; Hartopp, Richard; Ball, Jonathan; Hutt, Kate; Kennea, Nigel
Abstract : Objective: To undertake a case review of deaths in a 6-week period during the COVID-19 pandemic commencing with the first death in the hospital from COVID-19 on 12th of March 2020 and contrast this with the same period in 2019. Setting: A large London teaching hospital. Participants: Three groups were compared: group 1—COVID-19-associated deaths in the 6-week period (n=243), group 2—non-COVID deaths in the same period (n=136) and group 3—all deaths in a comparison period of the same 6 weeks in 2019 (n=194). Primary and secondary outcome measures: This was a descriptive analysis of death case series review and as such no primary or secondary outcomes were pre-stipulated. Results: Deaths in patients from the Black, Asian and minority ethnic (BAME) communities in the pandemic period significantly increased both in the COVID-19 group (OR=2.43, 95% CI=1.60–3.68, p<0.001) and the non-COVID group (OR=1.76, 95% CI=1.09–2.83, p=0.02) during this time period and the increase was independent of differences in comorbidities, sex, age or deprivation. While the absolute number of deaths increased in 2020 compared with 2019, across all three groups the distribution of deaths by age was very similar. Our analyses confirm major risk factors for COVID-19 mortality including male sex, diabetes, having multiple comorbidities and background from the BAME communities. Conclusions: There was no evidence of COVID-19 deaths occurring disproportionately in the elderly compared with non-COVID deaths in this period in 2020 and 2019. Deaths in the BAME communities were over-represented in both COVID-19 and non-COVID groups, highlighting the need for detailed research in order to fully understand the influence of ethnicity on susceptibility to illness, mortality and health-seeking behaviour during the pandemic.